Dehydroevodiamine Alleviates Doxorubicin-Induced Cardiomyocyte Injury by Regulating Neuregulin-1/ErbB Signaling - Song Jie; Guo Wenying; Sun Lebo (Cardiovascular Therapeutics)
Conclusion: DHE protects cardiomyocytes against DOX by regulating NRG1/ErbB pathway. DHE may be a potential agent for the prevention and treatment of DIC.